Haemodynamic assessment of right ventricular overload in pulmonary hypertension: old parameters still fit better than new ones. (25th November 2020) - Pereira, A; Santos, J.G; Loureiro, M.J; Ferreira, F; Almeida, A.R; Cale, R; Repolho, D; Pereira, H
Abstract: Introduction: Right ventricular (RV) adaptation to the increased pulmonary load is a key determinant of outcomes in pulmonary hypertension (PH). Pulmonary vascular resistance (PVR) is widely recognized as haemodynamic measure of RV overload. Cardiac filling pressure (CFP), RV stroke work (RVSW), pulmonary artery (PA) compliance and PA pulsatility index (PAPi) are emerging as new haemodynamic parameters to assess RV function. Aims: To assess the predictive value of CFP, RVSW, PA compliance and PAPi in PH and to compare it with standard haemodynamic parameters. Methods: Retrospective study including all consecutive right heart catheterizations performed from April/2009 to October/2019 in a PH referral centre. Procedures presenting PH were selected [mean pulmonary arterial pressure (mPAP) >20 mmHg, according to the new definition of the 6st World Symposium on PH]. CFP was calculated as [right atrial pressure (RAP) − pulmonary capillary wedge pressure], value >0.63 associated with RV failure; RVSW as CO / [(heart rate × (mPAP-RAP) × 0.0136], value <15; PA compliance [SV / pulmonary arterial systolic pressure (PASP) − pulmonary arterial diastolic pressure (PADP)], value <2.5]; PAPi [(PSAP − PDAP) / RAP, value <1.85]. Multivariate logistic regression was used to identify predictors of all-cause mortality. Receiver operating characteristic (ROC) curves and area under curve (AUC) were used to assess discrimination power. Results: From a total of 569 procedures, 470 fulfilled PH criteria: mean age 57.9±16.0 years, 67.7% female, 35.5% performed under pulmonary vasodilator therapy. Pre-capillary PH was diagnosed in 71.9% of cases. Chronic thromboembolic PH was the most common subtype (34.4%). Concerning standard haemodynamic parameters: mPAP was 39.0±12.0 mmHg, mean RAP 8.0±5.0 mmHg, mean RVP 7.5±5.0 uWood and CI 2.5±0.8 L/min/m 2 . Median value of CFP was 0.6 (IQR 0.4–0.8), RVSW 15.2 (IQR 9.7–25.0), PA compliance 2.1 (IQR 0.9–2.9) and PAPi 5.3 (IQR 3.2–8.5). All-cause mortality rate was 22.8%. Patients experiencing adverse events had lower values of cardiac index (2.3±0.6 vs 2.6±0.8 L/min/m 2, p<0.01), RVSW (11.2 vs 16.7, p<0.01) and PA compliance (2.2 vs 2.9, p<0.01) and higher values of PVR (10.0±5.5 versus 6.8±4.6 uWood, p<0.01) and mean RAP (9.9±6.1 versus 7.4±4.5, p<0.01). Multivariate logistic regression identified 2 independent predictors of adverse events: mean RAP (OR 1.08, 95% CI 1.02–1.13, p<0.01) and PVR (OR 1.11, 95% CI 1.06–1.17, p<0.01). According to the ROC curves, new haemodynamic parameters did not have acceptable discrimination power to adverse events occurrence (figure). Conclusions: In this study, new haemodynamic parameters to assess RV overload in PH were not independent predictors of adverse events as opposite to standard haemodynamic parameters. Further studies are needed to clarify their predictive value, as it has major implications for understanding the arterial load in diseases of the pulmonary circulation. Funding Acknowledgement: Type of funding source: None